Beyond "pains" and "gains": untangling the health consequences of probation - Michelle S. Phelps; Ingie H. Osman; Christopher E. Robertson; Rebecca J. Shlafer (BMC, 2022)
Abstract Background Research on the health consequences of criminal legal system contact has increasingly looked beyond imprisonment to understand how more routine forms of surveillance and punishment shape wellbeing. One of these sites is probation, the largest form of supervision in the U.S. Drawing on an interview study with 162 adults on probation in Hennepin County, MN, in 2019, we map how adults on probation understand the consequences of supervision for their health and how these self-reported health changes correlate with individual, social, and structural circumstances. Results Roughly half of participants described their health as having improved since starting probation, while the remainder were split between no change and worsened health. Examining both closed-ended survey questions and open-ended interview prompts, we find that the "gains" of supervision were correlated with substance use treatment (often mandated), reduced drug and alcohol use, increased housing and food security, and perceptions of support from their probation officer. However, these potentially health-promoting mechanisms were attenuated for many participants by the significant "pains" of supervision, including the threat of revocation, which sometimes impacted mental health. In addition, participants in the most precarious circumstances were often unable to meet the demands of supervision, resulting in further punishment. Conclusions Moving beyond the "pains" and "gains" framework, we argue that this analysis provides empirical evidence for the importance of moving social services outside of punishing criminal legal system interventions. People with criminal legal contact often come from deeply marginalized socio-economic contexts and are then expected to meet the rigorous demands of supervision with little state aid for redressing structural barriers. Access to essential services, including healthcare, food, and housing, without the threat of further criminal legal sanctions, can better prevent and respond to many of the behaviors that are currently criminalized in the U.S. legal system, including substance use.